CHARACTERISTICS OF LIPID BIOMARKERS (N-ALKANES, FATTY ACIDS, STEROLS, N-ALKANOLS AND ISOPRENOID) IN ESTUARINE SEDIMENTS OF MUARA ANGKE JAKARTA BAY AND CILINTANG-UJUNG KULON - Mohammad Agung Nugraha; Tri Prartono; Harpasis Slamet Sanusi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
ABSTRACT Lipid biomarkers as specific organic compounds can be used to evaluate the possible contribution of organic carbon from different sources or to trace the biological origin of molecules. The purpose of this research was to assess the contribution of sedimentary organic of origin based on the characteristics of lipid biomarkers in the Muara Angke Estuary-Jakarta Bay and Cilintang-Ujung Kulon. Single sediment sample were collected at the 10 cm deep from the top sediment. Those samples were extracted by soxhlet apparatus and fractioned prior to GC-MS analysis. All of those sediment showed different characteristics of biomarker (n-alkanes, fatty acid, sterol,n-alkanols and isoprenoid). They indicated the different of contribution of organic material inputs influenced by the activity of the upland and surrounding the estuary. Keywords: estuary sediment, GC-MS, lipids biomarkers